Rebecca's Promise - Eicher, Jerry S. (Eugene, Or. : Harvest House Publishers, 2009)
After accepting John Miller's marriage proposal, Rebecca is sent to her childhood home to care for her aunt, where she is confronted with the memories of her first love.
Keywords: Amish -- Fiction; Betrothal -- Fiction; Love stories; Fiction